Learning biomarker models for progression estimation of Alzheimer's disease - Schmidt-Richberg, Alexander; Ledig, Christian; Guerrero, Ricardo; Molina-Abril, Helena; Frangi, Alejandro; Rueckert, Daniel (PLoS ONE, 2016)
Being able to estimate a patient's progress in the course of Alzheimer's disease and predicting future progression based on a number of observed biomarker values is of great interest for patients, clinicians and researchers alike. In this work, an approach for disease progress estimation is presented. Based on a set of subjects that convert to a more severe disease stage during the study, models that describe typical trajectories of biomarker values in the course of disease are learned using quantile regression. A novel probabilistic method is then derived to estimate the current disease progress as well as the rate of progression of an individual by fitting acquired biomarkers to the models. A particular strength of the method is its ability to naturally handle missing data. This means, it is applicable even if individual biomarker measurements are missing for a subject without requiring a retraining of the model. The functionality of the presented method is demonstrated using synthetic and - employing cognitive scores and image-based biomarkers - real data from the ADNI study. Further, three possible applications for progress estimation are demonstrated to underline the versatility of the approach: classification, construction of a spatio-temporal disease progression atlas and prediction of future disease progression. Copyright:
CRIS-Team Scopus Importer:2023-03-08